Fortified buckwheat noodles as a potential replacement of locally produced noodles - Farzana, T; Hossain, FB; Orchy, TN; Mohajan, S; Fatema, J; Afrin, S (Bangladesh Journal of Scientific and Industrial Research, 2021)
The present study explored the possibility of formulating noodles with improved nutritious value and acceptable sensory properties using buckwheat (Fagopyrum esculentum) flour in supplementation of wheat flour and compared the developed noodles with locally available branded noodles in Bangladesh. Wheat flour was substituted with 10%, 20%, 30% and 40% whole buckwheat flour. Ash (1.95-2.16%), protein (13.45-17.04%), fat (0.55-0.78%), fiber (0.23-0.55%) and mineral contents increased with the increasing content of buckwheat flour in noodles preparation. On sensory evaluation, noodles formulated with 30% buckwheat flour were to be found acceptable and were characterized with higher mineral content along with the accession in ash, protein and fiber content up to 2.08%, 16.13% and 0.46% respectively, which outran the values of other locally available noodles. On sensory evaluation and nutritional point of view, it can be concluded that buckwheat noodles is a potential replacement of other available noodles in the local market of Bangladesh. Bangladesh J. Sci. Ind. Res.56(1), 17-24, 2021